OTAL BARLEY - WOLFE, R. I.; TAYLOR, R. L.; FARIS, D. G. (Canadian Journal of Plant Science, 1987)
Otal is a six-rowed spring feed barley (Hordeum vulgare L.) developed and released in Alaska by the United States Department of Agriculture and the state Agricultural and Forestry Experiment Station at Palmer. Otal was developed from a cross of the Finnish cultivar Otra, and a breeding line from the Weibullsholm Plant Breeding Institute, Sweden. It was identified at the Agriculture Canada Research Station at Beaver-lodge in Alberta as having promise in the Peace River region for its combination of earliness and high yield, and was licensed for sale in Canada.Key words: Cultivar description, barley, Hordeum vulgare L. early-maturity